IDT252 : Computer aided industrial design II / Faculty of Art and Design - UiTM, Faculty of Art and Design (Universiti Teknologi MARA (UiTM), 2023)
1. This course is developed to teach students on how to use the Computer Aided Industrial Design mechanical design automation software in building parametric models of parts and assemblies and how to make drawings of those parts, assemblies and 3D machining and rapid prototyping standard. 2. This course also insulates professional practise while featuring rich application aspect of prototyping software discerning to reasonable length of prototyping expertise,Therefore,the focus of this course will consider the fundamental skills and concepts central to the successful use of computer Aided Industrial Design. 3. This course is equipped with a computer-aided manufacturing (CAM) program for rapid prototyping machines relevant for concurrent design related industries.The technical aspects of this course will incorporate generic 3D data(such as IGES, DXF [3D], and STL) for cross manipulation in rapid prototyping machines.Inclusively,with the essential information given,learners will have better understanding and strategy in order to exploit machine advantages for design projects.